Delimitation of the segmented trapdoor spider genus Luthela gen. nov., with comments on the genus Sinothela from northern China (Araneae, Mesothelae, Liphistiidae) - XU, XIN (Magnolia Press, 2022)
10.11646/zootaxa.5091.1.5